Pengaruh Estetik Video Game terhadap Minat Gamer dengan Genre Survival - Remington Huan, Chayen; Anggriani Adnas, Diny (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2023)
Video games have many genres and for this research, the author focuses on survival genre Video games. Video games with the survival genre give players freedom and try to survive in the world provided by the video game. Because players are free to explore in the video game, the visuals or graphics in the world in the video game will greatly affect the player's interest, but there are survival video games that have good visuals but don't have many interests like Fallalypse and Age of Survival where both video games have a Very Negative rating. However, there is one survival video game that doesn't have good visuals and only relies on unique gameplay but has a lot of interest and that video game is Minecraft. The purpose of this research is to find out the interest of players or gamers in video games in the survival genre. This study used quasi-experimental and qualitative methods on 14 participants with an age range of 18-26 years. After the quasi-experiments and qualitative were completed, the authors were able to receive one conclusion about gamers’ preference in survival video games, gamers prefer playing survival video games. which are not too realistic or similar to the real world in terms of difficulty, but gamers prefer to see visuals or graphics that are realistic or similar to the real world.